ANALISIS PENGELOLAAN KEUANGAN DESA ( STUDI EMPIRIS PADA PEMERINTAHAN DESA GUNUNGSARI KECAMATAN DAWARBLANDONG KABUPATEN MOJOKERTO ) - ANDRIAN, AGIL (Jurnal Akuntansi AKUNESA, 2017)
The purpose of this study was to determine the suitability of the financial management of the Gunungsari Village with the principles, rules and human resources conducting financial management. This research was conducted by qualitative descriptive method of phenomenology approach by conducting interviews to the informants concerned plus by looking at the evidence report on the realization of use village funds in 2015 as well as evidences supports. The results showed that the government has committed  on principles of financial management of the village but still lacking in conformity with human resources responsibilities. Keywords: Financial management, Rules, Human Resources